2010
DOI: 10.1002/art.27548
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord mesenchymal stem cell transplantation in severe and refractory systemic lupus erythematosus

Abstract: Objective. Umbilical cord (UC)-derived mesenchymal stem cells (MSCs) have shown marked therapeutic effects in a number of diseases in animal studies, based on their potential for self-renewal and differentiation. No data are available on the effectiveness of UC MSC transplantation (MSCT) in human autoimmune disease. This study was undertaken to assess the efficacy and safety of allogeneic UC MSCT in patients with severe and treatment-refractory systemic lupus erythematosus (SLE).Methods. We conducted a single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
318
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 430 publications
(335 citation statements)
references
References 40 publications
10
318
0
7
Order By: Relevance
“…All patients showed autoimmune disease remission and hence, presented a case for the discontinuation or reduction of the administered immunosuppressive drugs. Neither duration of the treatment nor patient observation period (from 12 to 18 months) indicated correlation with the appearance of serious side effects [38]. In this study, as in another study by Sun et al, the authors noted a disorder in the structure and functioning of the own MSCs of patients suffering from Systemic Lupus Erythematosus [38,39].…”
Section: Mesenchymal Stem Cells In the Autoimmune Diseasessupporting
confidence: 49%
“…All patients showed autoimmune disease remission and hence, presented a case for the discontinuation or reduction of the administered immunosuppressive drugs. Neither duration of the treatment nor patient observation period (from 12 to 18 months) indicated correlation with the appearance of serious side effects [38]. In this study, as in another study by Sun et al, the authors noted a disorder in the structure and functioning of the own MSCs of patients suffering from Systemic Lupus Erythematosus [38,39].…”
Section: Mesenchymal Stem Cells In the Autoimmune Diseasessupporting
confidence: 49%
“…Under stress conditions, MSCs decrease local inflammation and participate in tissue repair and regeneration by secreting cytokines, chemokines, and extracellular matrix proteins [3,4]. Previous data from our group and others demonstrated the immunosuppressive and anti-inflammatory effects of MSCs in the treatment of several animal disease models, including autoimmune diseases [5][6][7]. As a result of these unique qualities, MSCs are attractive candidates in stem cell-based strategies for tissue repair.…”
Section: Introductionmentioning
confidence: 90%
“…Significantly, this study demonstrated a therapeutic effect for at least 12 months, suggesting a longer lasting benefit compared to our cases. In another study, MSCs that had been derived from umbilical cords of nonrelated children were transplanted into 16 patients with SLE (14). The treatment led to meaningful clinical improvement and to a reduction of autoantibody titers.…”
mentioning
confidence: 99%